A new family of Cavilabiata from the Lower Cretaceous Yixian Formation, China (Odonata: Anisoptera) - Lin, Qi-Bin; Huang, Di-Ying; Nel, A. (Zootaxa, 2007)
A new genus Nodalula gen. nov. and species Nodalula dalinghensis gen. et sp. nov. is described on the basis of a nearly complete specimen from the Lower Cretaceous of North-east China. Its special pattern of wing venation differs from those of the known Mesozoic Cavilabiata genera and allows us to include it in the new family Nodalulaidae within the Neobrachystigmata.